Association Between Locus Of Control And Work Satisfaction ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Work satisfaction or job satisfaction is an important factor for any organization to ensure low employee  turnover and promote their company via their employees as a good place to work. As per many researches, there is a  direct relationship between Locus of Control (LOC) and Work Satisfaction Level. Objectives: The objectives of this study  were: (i) to identify the association between Locus of Control of hospitality professionals and years of experience; (ii)  to identify the work satisfaction or job satisfaction levels of hospitality professionals; and (iii) to identify the association  between Locus of Control and Work Satisfaction levels of hospitality professionals. Methodology: The present descriptive  research was conducted on 103 hospitality professionals of Delhi-NCR region. The sampling technique was convenience  sampling. To measure Locus of Control, two existing tools were used as a reference to develop a new similar tool and  to measure the Job Satisfaction levels of hospitality professionals, eNPS i.e., Employee Net Promoter Score was used.  Mean, SD, Percentage, z-test and Pearson’s Correlation Coefficient were applied for statistical analysis and the data  was analysed based on ‘years of experience.’ Results: The results of eNPS showed that 43.69 % of the respondents  were Promoters, 40.78 % of the respondents were Passives and 15.53 % of the respondents were Detractors. Mean Job  Satisfaction Levels of Hospitality Professionals came out be 7.94 ± 1.79 (out of 10) indicating that mean respondents  are Passives. z-test was done at 1% level of significance to test the hypothesis for association between Locus of Control  (LOC) and years of experience, for which, null hypothesis was rejected [calculated value of z = 4.228 at 1% level of  significance which is greater than 2.58 (critical value of z)], hence, proving that there is a significant difference in  the Locus of Control of hospitality professionals with over 5 years of experience and those with less than 5 years of  experience. Pearson’s Product Moment Correlation Coefficient was calculated to recognize the association between  Locus of Control (LOC) and Work/Job Satisfaction levels, for which the value of r = -0.069 indicating that there is no  correlation between the two variables. Conclusion: It can be concluded from this study that personality type (Locus  of Control) individually is not the deciding factor for job satisfaction levels of hospitality professionals but maybe the  result of other factors.
Keywords: Locus of Control; Hotels; Hospitality; Experience; Work Satisfaction